Using Real Options for the Evaluation of Venture Projects - Alexander Baranov; Elena Muzyko (Gadjah Mada International Journal of Business, 2016)
This paper considers the peculiarities of the application of the real options method for assessing the economic efficiency of venture investments in innovative projects from the venture fund’s position. The results of the practical use of the author’s approach for the evaluation of venture investments with real options are analyzed. The paper shows the applicability of the real options concept to the valuation of the effectiveness of venture capital investments. The use of the real options method raises the accuracy of the estimation and enhances the instruments of the venture fund in evaluating the economic efficiency of innovative projects.